(untitled) (Paris, 1977)
This book introduce transfer of technology by multinational corporations and absortive capacity of the developing countries. Relations of subsidiaries with the scientific technical and industrial environment in the host country...
Keywords: Chuyển giao công nghệ,Technology transfer